Problem Based Character Education for Street Children in Satoe atap Semarang Community - Paramadita, Kidung; Rifai RC, Ahmad; Suminar, Tri (Journal of Nonformal Education, 2018)
A Character Education for street children has not been well developed. There are no learning methods which are used by educators effectively. This research and development (R D) were aimed to describe character education that occurs implicitly and factually, resulting in problem-based character educatoin which was effective for street children, as well as to know the practicality and the effectiveness of problem-based character education guidebooks for street children. The factual conditions for character education were obtained by interview, observation and documentation. The conceptual guide book was validated by 2 experts and 3 practitioners. The guidebook for the implementation of character education includes the planning stage; implementation stage; closing stage. The guideline for implementing character education was efectively used to improve the street children character. It was recommended for volunteers as the main learning source to pay more attention to the learning process and the character education goals which would be achieved, they must follow the stages of the implementation guide, made the children accustomed to being more sensitive and repeat the characters which would be achieved so that those characters education develop well